Reserve allocation of high-penetration renewable energy grids considering frequency security - Liu, Fang; Su, Yunche; Liu, Yang; Chen, Dawei; Chen, Wei; Kuang, Li (Frontiers in Energy Research, 2024)
As the penetration rate of renewable energy in the power grid continues to rise, the reserve criteria for traditional power grids dominated by synchronous generators (SGs) have difficulty meeting system frequency security requirements. This study proposes a frequency security constrained optimization approach for the allocation of reserve capacity in high-penetration renewable energy grids that utilize multitype reserve resources, including SGs and nonsynchronous units, to address the frequency security issue. First, strategies and models for expanding the sources of frequency regulation reserves are analyzed, including various types of renewable energy generation, such as wind turbine (WT) curtailment and the combination photovoltaic (PV) cells and battery storage. A refined reserve criterion is then proposed that considers multidimensional evaluation indices from both operational economy and frequency security aspects. Finally, a bilevel optimization model for reserve capacity allocation on multiple timescales that considers frequency security is constructed. The rationality and effectiveness of the proposed reserve allocation scheme were verified using a practical power grid in Southwest China.